Visual fatigue and discomfort after stereoscopic display viewing - Zhang, Li; Jonas, Jost B. (Acta ophthalmologica, 2013)
Abstract. Purpose: Different types of stereoscopic video displays have recently been introduced. We measured and compared visual fatigue and visual discomfort induced by viewing two different stereoscopic displays that either used the pattern retarder-spatial domain technology with linearly polarized three-dimensional technology or the circularly polarized three-dimensional technology using shutter glasses. Methods: During this observational cross-over study performed at two subsequent days, a video was watched by 30 subjects (age: 20-30 years). Half of the participants watched the screen with a pattern retard three-dimensional display at the first day and a shutter glasses three-dimensional display at the second day, and reverse. The study participants underwent a standardized interview on visual discomfort and fatigue, and a series of functional examinations prior to, and shortly after viewing the movie. Additionally, a subjective score for visual fatigue was given. Results: Accommodative magnitude (right eye: p < 0.001; left eye: p = 0.01), accommodative facility (p = 0.008), near-point convergence break-up point (p = 0.007), near-point convergence recover point (p = 0.001), negative (p = 0.03) and positive (p = 0.001) relative accommodation were significantly smaller, and the visual fatigue score was significantly higher (1.65 ± 1.18 versus 1.20 ± 1.03; p = 0.02) after viewing the shutter glasses three-dimensional display than after viewing the pattern retard three-dimensional display. Conclusions: Stereoscopic viewing using pattern retard (polarized) three-dimensional displays as compared with stereoscopic viewing using shutter glasses three-dimensional displays resulted in significantly less visual fatigue as assessed subjectively, parallel to significantly better values of accommodation and convergence as measured objectively.